Thermal Neutron Induced Capture and Fission Gamma-Ray Emission Measurements and Simulation Methods - Danon Yaron; Keparutis Katelyn; Parker Ian; Barry Devin (EPJ Web of Conferences)
In order to validate evaluated capture gamma-ray cascade data used in coupled neutron-photon transport simulations, measurements of thermal neutron induced capture were performed as a function of neutron time-of-flight (TOF). A large 16-segment NaI(Tl) gamma-ray multiplicity detector was used with a 14-bit digitizer to record event-by-event gamma-ray energy deposition. Histograms of the gamma-ray emission spectra in each of the detectors and coincidence spectra of all 16 detectors were generated for analysis. The spectra were produced by gating on specific TOF regions that correspond to either thermal neutrons (0.01 - 1 eV) or energies of specific resonances in the sample material. The experimental results were compared to simulations using a modified version of MCNP6.2 that can read capture gamma-ray cascades from a file, transport them through the detector geometry and output event-by-event energy deposition in each detector similarly to the processed experimental data. The Monte Carlo code, DICEBOX, was used to generate the capture gamma-ray cascades using ENSDF evaluated gamma-ray energies and intensities and RIPL-3 model parameters. The experiment was also compared to spectra produced by MCNP6.2 using ENDF/B-VIII.0 evaluated photon production data. It was observed that in some cases the ENDF/B-VIII.0 data can produce a reasonable single detector spectrum but coincidence modeling is not currently possible in standard MCNP6.2 calculations.